CpG plus radiotherapy: a review of preclinical works leading to clinical trial - Mason, Kathy A.; Hunter, Nancy R. (Frontiers in Oncology, 2012)
Studies performed 3 decades ago in our laboratory supported the hypothesis that radiation efficacy may be augmented by bacterial extracts that stimulate non-specific systemic antitumor immune responses. Application to the clinic was halted by unacceptable side effects and toxicities resulting from exposure to whole bacterial pathogens. Later scientific advances demonstrated that DNA isolated from bacteria was immunostimulatory and could be reproduced with synthetic oligodeoxynucleotides (ODNs), thus fueling the transition from bugs to drugs. Unmethylated CpG motifs within bacterial DNA induce activation of Toll-like receptor 9 and subsequently activate antigen-specific cellular immune responses. CpG ODNs have demonstrated favorable toxicity profiles in phase I clinical trials. We showed that this potent immunoadjuvant can be used in combination with radiation therapy to enhance local and systemic responses of several murine tumors. Studies demonstrated that enhanced tumor response is mediated in part by the host immune system. Antitumor efficacy was diminished in immunocompromised mice. Animals cured by combination of radiation and CpG ODN were resistant to subsequent tumor rechallenge. This body of work contributes to our understanding of the dynamic interplay between tumor irradiation and the host immune system and may facilitate translation to clinical trials.